Borra de café: análise da caracterização termoquímica, do processo de elutriação, secagem, peletização e da mistura com outros resíduos - Rocha, Thalyne de Almeida Ferreira (2023)
For the reuse of the spent coffee grounds, this thesis has two main strategies, the first is to evaluate its granulometry as a function of the thermal degradation behavior, the elutriation, drying process, pelletization and the spent coffee grounds combustion. And the second is to evaluate mixtures of spent coffee grounds with orange pomace and sugarcane bagasse in the production and the combustion of pellets. In the first part, the influence of the spent coffee grounds granulometry on the combustion behavior was identified by TG and DrTGA analyses, in addition, it was observed that the spent coffee ground breaks up, producing fines when it is submitted to agitation of the fluidized bed. Furthermore, increasing the air velocity, the temperature and the vibrational amplitude and frequency (in a vibrofluidized bed) favors the elutriation as well as the drying process of this material. It was also verified that the drying process of the spent coffee grounds, from 45% to 0.25% of moisture content (w.b.), occurs in the first period of decreasing rate, where the external drying conditions control the process. Also in this time interval, the particulate diameter does not have a significant influence on the drying behavior. With the dried spent coffee grounds, pellet fuels were produced with excellent results in the quality tests. Being that, better results were obtained when smaller was the particulate diameter, due to a greater surface area that leads to an increase in solid-solid forces. In the second part, it was found that spent coffee grounds have a positive influence on the mechanical and thermal quality of pellets of both mixture, sugarcane and orange bagasse. Improving transportation and impact resistance, less moisture absorption and an increase in the energy released in combustion reactions. The main conclusions of this thesis were that the best conditions for elutriation and drying of spent coffee grounds in a vibrofluidized bed are those that favor the generation of fines, which makes more resistant pellets with similar thermal performance. Moreover, spent grounds coffee can be used in a mixture with other wastes, such as sugarcane and orange bagasse, to produce better quality pellets.